(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Recent years have seen a transition in consumer’s buying behaviour for foods having better nutrition, transparent claims with more clean processes and ingredients. Objective: This paper aims at understanding the factors that influence consumers’ food buying behaviour, perceptions and healthy food choices. Methodology: Quantitative research was done in restricted cities of India through online media. Information was collected (targeting21-40 years age group) from 470 respondents (64.4% males and 35.6% females). Responses were recorded through an online circulated questionnaire containing 15 close-ended questions, which were statistically analyzed through MS-excel using graphical representations. Results: A greater inclination was seen towards healthier options in staples such as multigrain flour. The survey findings reported that around 34.5% of consumers are taking the product quality claims and source of ingredients seriously, and also consumers do care about the environmental impact of the products, with 83.62% respondents preferring products which are environment friendly and socially responsible. Conclusion: It can be concluded that there has been a considerable shift towards healthier food choices. Companies should focus on strategies to promote healthier choices, clean labels, more transparency and reduce their environment and social burden. Marketing strategies may also be geared towards promotion of products through online platforms since millennia’s, who compromise 48% of work force spend their major time online.